Measuring the effects of guided clinical reasoning on the Advanced Nursing Process quality, on nurses' knowledge and attitude: Study protocol - Claudia Leoni‐Scheiber; Hanna Mayer; Maria Müller‐Staub (Wiley, 2019)
Abstract Aim This article is a report of a study protocol designed to examine the effects of guided clinical reasoning on the quality of the Advanced Nursing Process-the evidence‐based version of the traditional nursing process. It aims to describe the theoretical framework-Kirkpatrick's evaluation model, the key concepts and the instruments for the planned study. Design A complex experimental intervention study using data and method triangulation is proposed. Methods Registered Nurses (N = 92), nursing records (N = 180) and 24 patients will be included. Nurses' knowledge and attitude will be evaluated by questionnaires/tests, their clinical performance by observations. Patients' perspective will be addressed by qualitative interviews and patient records by using the instrument Quality of Diagnoses, Interventions and Outcomes revised (Q‐DIO R). Discussion Kirkpatrick's model (including quantitative and qualitative methods) is providing evaluations from different perspectives on the quality of the Advanced Nursing Process and on intervention effects.